Vascular mechanisms in acute unilateral peripheral vestibulopathy: a systematic review - Simões, João (2021)
Acute unilateral peripheral vestibulopathy (AUPVP) is a frequent cause of vestibular loss. Several aetiologies have been proposed, but the exact mechanism remains unknown. The aim of this study is a systematic analysis of the literature evaluating the vascular aetiology of AUPVP. A systematic literature search was performed in PubMed, Cochrane Library and Embase, including articles published from January 1st, 2010 to November 30th, 2020. Two reviewers independently selected articles investigating a link between AUPVP and vascular disease. The following information was extracted: year of publication, country, level of evidence, assessed vascular risk factors and number of patients. A total of 450 articles was obtained. Eleven articles were retained with 100% agreement between the two reviewers. In a pooled population of 805 patients, the main results were the higher neutrophil to lymphocyte ratio and higher prevalence of vascular risk factors among AUPVP patients. A meta-analysis was not performed because the studies were too heterogeneous in terms of methodology. Indirect arguments for vascular mechanisms in AUPVP were found. These findings indicate that larger prospective well-controlled studies are needed to clarify the vascular aetiology of AUPVP.